Nasopharyngeal polyp excision in a domestic cat: Case report (Research, Society and Development, 2025)
The present study reported a clinical case of a nasopharyngeal polyp in a domestic cat, a benign inflammatory condition that caused upper respiratory tract obstruction and impaired the animal’s well-being. This work aims to describe and analyze a case of a nasopharyngeal polyp in a domestic feline, integrating clinical, diagnostic, therapeutic, and prognostic aspects and correlating the findings with recent data from specialized literature.The methodological approach was based on a descriptive case report, prepared from clinical, laboratory, radiographic, tomographic, endoscopic, and histopathological data. The animal, a four-year-old neutered male domestic cat, presented inspiratory dyspnea, stertor, and persistent bilateral nasal discharge, which worsened with climate variations. Computed tomography revealed filling of the nasal cavities with fluid-attenuating material and partial lysis of the nasal turbinates, while rhinoscopy and the subsequent histopathological examination confirmed the presence of a non-neoplastic inflammatory polyp.The attempt to remove the mass by traction was interrupted due to the risk of anatomical injury; thus, conservative management was instituted, consisting of daily nasal lavage with warm saline. After adopting this approach, progressive clinical improvement was observed, including reduced respiratory discomfort and decreased nasal secretion, with maintenance of appetite and normal behavior. This case highlights that, although surgical intervention is considered the treatment of choice for nasopharyngeal polyps, in certain clinical situations the use of palliative and individualized measures can be effective in partially restoring respiratory function and promoting satisfactory quality of life.